Casual Dress “Plumeria ECORI” Menggunakan Teknik Ikat Celup dan Ecoprint - Wdyaningsih, nida; Asiatun, Kapti (Practice of Fashion and Textile Education Journal, 2024)
This research highlights the role of creativity as an important skill in creating original and imaginative work. In the context of casual fashion, creativity is realized through ecoprinting techniques and shibori with natural dyes. The innovative product called Plumeria ECORI reflects the values of devotion to Allah SWT, reflected in the meaning of motifs and clothing designs. The application of Research and Development methods that focus on PPE (Planning, Production and Evaluation) provides a systematic framework in fashion design, production and evaluation. The planning process involves selecting designs, materials, and pre-treating the fabric using scouring and mordanting techniques. The production stage involves executing the design using eco-printing and shibori techniques, with natural dyes such as jolawe, indigo, and tegeran. Evaluation involves assessing the motif name, motif meaning, motif components, color combination, total look, clothing silhouette, clothing details, clothing suitability, and product price. Evaluation results from the community, especially in Malaysia, show a positive response to Plumeria ECORI. Overall, innovation in casual clothing with eco-printing and shibori techniques proves that creativity provides aesthetic and economic value. The PPE method approach makes a significant contribution to the development of creative and innovative clothing manufacturing techniques using natural dyes.